2019
DOI: 10.1002/slct.201900125
|View full text |Cite
|
Sign up to set email alerts
|

Sublattice Energy Cluster Construction for The Enhancement of NIR Photocatalytic Performance of LiYF4: Tm@TiO2

Abstract: In this work, a stratagem of improving the photocatalytic performance of TiO 2 under NIR irradiation was illustrated by the combination of TiO 2 with upconversion (UC) luminescent materials that present high intensity of UV band emission resulted from the sublattice energy clusters in tetragonal LiYF 4 : Tm UC matrix. The sublattice energy clusters were constructed by doping high concentration Yb 3 + into tetragonal LiYF 4 : Tm. 347 nm emission intensity of Tm 3 + were enhanced dramatically with the rising of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…Rare-earth (RE)-doped upconversion luminescence nanoparticles (UCLNPs) are an important kind of functional nanomaterial. They exhibit excellent performance and have evoked much attention due to their wide promising applications in temperature sensors, solar energy conversion, , biomedical imaging, biomass detection, medical tracers, , photodynamic therapy, ,, drug-targeted delivery, photocatalysis, , anticounterfeiting, , etc. Nano NaYF 4 :RE is an outstanding representative of these nanomaterials, , although the relatively poor UCL performance is still the main obstacle for their application.…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth (RE)-doped upconversion luminescence nanoparticles (UCLNPs) are an important kind of functional nanomaterial. They exhibit excellent performance and have evoked much attention due to their wide promising applications in temperature sensors, solar energy conversion, , biomedical imaging, biomass detection, medical tracers, , photodynamic therapy, ,, drug-targeted delivery, photocatalysis, , anticounterfeiting, , etc. Nano NaYF 4 :RE is an outstanding representative of these nanomaterials, , although the relatively poor UCL performance is still the main obstacle for their application.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the UCL mechanism of sublattice energy cluster construction and crystal field manipulation were revealed that may be an inspiration for high efficient UC luminescence materials design and preparation. Keywords LiYF 4 ; rare earth; sublattice structure; crystal field manipulation; upconversion luminescence 1 引言 稀土离子具有丰富的不饱和 4f 层核外电子能级结 构, 在长波光源激发下可实现反斯托克的短波光发射 [1] , 具有发射光波长分布范围广、发射谱带宽以及发射波长 可调控等优良特性, 使得稀土上转换发光材料在防 伪 [2][3][4] 、生物检测 [5,6] 、高分辨成像 [7][8][9] 、光动力治疗 [10,11] 、 药物靶向释放 [12,13] 、能源转换 [14,15] 、光催化 [16][17][18] 、光解 水 [19][20][21] 、光电器件 [22][23][24][25] 、温度传感器 [26,27] 等领域有着广 阔的潜在应用前景 [28] , 其成为近年发光材料领域研究 的热点 [29] . 当前限制稀土上转换发光材料应用的主要 瓶颈是可控发射波长、足够强的荧光强度和满足应用要 求的荧光寿命等上转换发光性能.…”
unclassified